2008
DOI: 10.3382/ps.2007-00327
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Twice-a-Day Feeding Regimen After Photostimulation on the Reproductive Performance of Broiler Breeder Hens

Abstract: Broiler breeder hens are typically provided a restricted amount of feed once a day. This feed is rapidly consumed; therefore, the hens fast for an extended period of time before their next feeding. In the current research, the effects on reproductive performance of implementing a twice-a-day vs. a once-a-day feeding program after photostimulation were investigated. Pullets and cockerels were reared on a skip-a-day feeding program. Pullets were weighed at 20 wk of age and then distributed into 30 laying pens su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
18
2
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 20 publications
11
18
2
9
Order By: Relevance
“…At the same time the present finding is also supported by the report of [27] who indicated that twice and thrice a day feeding regimens rather than once a day improved egg production rate. The current finding also coincides with the report of [28,29] who reported that chicken fed twice a day produced more eggs compared with chicken fed once a day and the chicken received their feed 2 or 3 times per day laid 4.8 eggs more than those that fed one time per day [30]. Also indicated that feeding 3 times per day increased the percentage of chicken daily egg production.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time the present finding is also supported by the report of [27] who indicated that twice and thrice a day feeding regimens rather than once a day improved egg production rate. The current finding also coincides with the report of [28,29] who reported that chicken fed twice a day produced more eggs compared with chicken fed once a day and the chicken received their feed 2 or 3 times per day laid 4.8 eggs more than those that fed one time per day [30]. Also indicated that feeding 3 times per day increased the percentage of chicken daily egg production.…”
Section: Discussionsupporting
confidence: 91%
“…Broiler breeder hens fed once a day in the afternoon had more egg production than those fed once a day in the morning (Farmer et al, 1983a;Brake and Peebles, 1986;Wilson and Keeling, 1991). Spradley et al (2008) reported that broiler breeders fed twice a day laid more and heavier eggs through 42 weeks of age than those fed once a day. They believed that increased egg weight was related to providing feed later in the day (3:00 PM).…”
Section: Discussionmentioning
confidence: 99%
“…They believed that increased egg weight was related to providing feed later in the day (3:00 PM). Moradi et al (2013) evaluated hens fed once a day at 6:15 AM and a twice a day feeding (at 6:15 AM and 12:15 PM) and Taherkhani et al (2010) evaluated hens fed once a day at 7:30 AM and twice a day feeding (at 7:30 AM and 11:30 AM), both authors reported that broiler breeders fed twice a day laid more and heavier eggs than those fed once a day. The influence of increasing feeding frequency may be related to a reduction in the fasting period during the day-light cycle (Moradi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations